RELIGIOSITY AS A MODERATION OF THE EFFECT OF INTELLECTUAL AND SPIRITUAL QUOTIENT ON EMPLOYEE PERFORMANCE - Noegroho, Andro Dewantara; Wulansari, Nury Ariani (Universitas Negeri Semarang, 2020)
The purpose of this study is to examine and Determine the moderating effect of religiosity from the effect between intellectual intelligence and spiritual intelligence on the performance of employees of state-owned bank branches conventional Tegal. This study took a sample of 115 employees using a multi-stage type of probability sampling technique, the which is a combination of proportional sampling and random sampling techniques. Data collection method is done by distributing questionnaires. The method of data analysis uses descriptive statistical tests and SmartPLS 3.0 software. The results of this study intellectual intelligence that has a positive effect on employee performance. Likewise, with spiritual intelligence has a positive effect on employee performance. In the moderation test, religiosity is not Able to moderate the relationship of intellectual intelligence on employee performance religiosity meaning that weakens the relationship, hypothesis 3 is rejected. Then, religiosity is Able to Strengthen the relationship of spiritual intelligence on employee performance hypothesis 4 is accepted meaning. Suggestions from this study, employees of conventional state-owned bank branch offices in Tegal city are expected to be Able to empower Reviews their intelligence in order to be Able to improve the level of performance in accordance with the company?s standards and for the management of conventional state -owned bank branch offices in Tegal city always provide motivation and establish communication with employees so that employees continue to maintain intellectual intelligence and spiritual intelligence in the work environment.